Lakon Brajadenta Brajamusthi: Sebuah Respon terhadap Lakon Brajadenta Mbalela - Saputra, Sumantri Adi; Kiswantoro, Aneng (Institut Seni Indonesia Yogyakarta, 2022)
AbstrackThis research aims to portray the origins of Raden Brajadenta and Raden Brajamusthi, as well as their death by Raden Gathutkaca. For the purpose, initial observations were made by watching shadow puppet performances and studying its literature. In addition, interviews with notable masters of Yogyakarta-style puppetry were conducted for more story references. The asma kinarya japa approach was used as a concept for compiling a new story adaptation. Asma kinarya japa is an approach used to track down the etymology of characters’ names in a shadow puppet performances. Microcosmical and macrocosmical context-based interpretation of meanings were derived. Afterwads, the Brajadenta Brajamusthi puppet performance with story adaptation was composed. The puppet master’s ideas were expressed in themes, main ideas, characterizations, settings, and plots of the story. The results indicate that the Braja sometimes originate from the magical power of Aji Gandawastra belonged to Prabu Pandhu which was given to Prabu Tremboko. The theme conveyed in the Brajadenta Brajamusthi performance is life perfection. This work conveys the idea that Brajadenta and Brajamusti originating from Aji Gandawastra with the wind aspect in themselves, ultimately, achieve life perfection by uniting with the ruler of the wind in Raden Gathutkaca.AbstrakTujuan penciptaan karya ini untuk memaparkan asal-usul Raden Brajadenta dan Raden Brajamusthi, serta peristiwa kematian mereka oleh Raden Gathutkaca. Untuk mencapai tujuan tersebut dilakukan observasi awal melalui pengamatan terhadap pertunjukan wayang kulit dan studi pustaka. Selanjutnya dilakukan wawancara dengan tokoh pedalangan gaya Yogyakarta untuk menambah referensi cerita. Pendekatan asma kinarya japa digunakan sebagai konsep menyusun sanggit baru. Asma kinarya japa merupakan pendekatan yang digunakan untuk menelusuri arti nama-nama tokoh dalam sebuah lakon wayang berdasarkan etimologi. Kemudian dari arti tersebut ditafsirkan maknanya atas dasar konteks, baik konteks mikrokosmos maupun makrokosmos. Langkah terakhir ialah penyusunan lakon Brajadenta Brajamusthi menggunakan teori sanggit lakon. Gagasan pengkarya dituangkan dalam tema, gagasan pokok, penokohan, setting, dan alur. Berdasarkan hasil pengamatan dan analisis, didapat asumsi bahwa kadang Braja berasal dari daya kesaktian Aji Gandawastra milik Prabu Pandhu yang diberikan kepada Prabu Tremboko. Tema yang akan disampaikan dalam lakon Brajadenta Brajamusthi ialah kesempurnaan hidup. Jadi karya ini menyampaikan sebuah pemikiran bahwa Brajadenta dan Brajamusti yang berasal dari Aji Gandawastra dengan aspek angin dalam diri mereka, pada akhirnya mencapai kesempurnaan hidup dengan cara bersatu dengan penguasa angin yang ada dalam diri Raden Gathutkaca.